Wydzielenie kontraktowe funkcji jako przykład zmiany w przedsiębiorstwie - Matejun, Marek (Contracted outsourcing of function as an example of change in enterprise, 2006)
Using of contracted outsourcing causes transferring functions previous realized by internal services of enterprise in favor of external supplier. The article presents reasons, aims and organizational aspects of outsourcing of accountancy and tax advises function in SMEs sector.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 472-481